The derivatives’ market: world trends and prospects - T K Blokhina (RUDN Journal of Economics, 2015)
In article are considered problems of progress of the world derivative market which for last years has increased volume of the turn up to catastrophically huge parameters are analyzed, significantly higher than world GDP. It calls into question reliability of a world financial system as the vast majority of these financial tools addresses on the market and consequently is not a subject to any regulation or the control. The decision of these problems lays, in opinion of the author, in creation of uniform system of an exchange turn of all types of derivative financial tools, that should match the volume-produced derivatives and real underlying assets, underlying.